Function of Uric Acid Transporters and Their Inhibitors in Hyperuricaemia - Sun, Hao-lu; Wu, Yi-wan; Bian, He-ge; Yang, Hui; Wang, Heng; Meng, Xiao-ming; Jin, Juan (Frontiers in Pharmacology, 2021)
Disorders of uric acid metabolism may be associated with pathological processes in many diseases, including diabetes mellitus, cardiovascular disease, and kidney disease.Some diseases can further increase uric acid levels and their accumulation in the body, leading to a vicious cycle.Oxidative stress, lipid metabolism disorders, and renin-angiotensin axis play a critical role in the progression of urate-related diseases.However, there is still a lack of effective clinical treatment for hyperuricemia.The study of uric acid transporters and their inhibitors provides a new idea for the treatment of clinical hyperuricemia.According to previous research results, SLC17A1, SLC17A3, ABCG2, SLC22A11, SLC22A12, SLC2A9, PDZK1, SLC22A7, and SLC16A9 were closely related to serum uric acid level in vivo.The mutations at different sites of the transporters have different effects on uric acid metabolism and excretion.With transporter as the target, the researchof transporter inhibitor will provide a better prospect for the clinical treatment of hyperuricemia.The purpose of this paper is to provide theoretical support for the scientific research on hyperuricemia and related diseases, and to improve the treatment by changing the uric acid transport.